The Role of Micronutrients (Zinc, Vitamin A, C, D and Iron) in Preventing Infectious Diseases in Disaster-Affected Populations: A Literature Review - Durry, Fara Disa; Sukma Sahadewa; Zulfan Febriawan; Prasetyaning Estu Pratiwi; Lionesya Sukma Winata (Universitas Wijaya Kusuma Surabaya, 2026)
Background: Micronutrient deficiencies significantly increase vulnerability to infectious diseases, partiularly among disaster-affected populations with limited access to food and healthcare. Despite this, micronutrient interventions are rarely prioritized in emergency health protocols, especially in countries like Indonesia. Objective: This review aims to examine the role of micronutrients in preventing infectious diseases in populations affected by disasters, based on an analysis of primary research articles. Methods: A narrative thematic literature review was conducted using databases such as PubMed, ScienceDirect, and Google Scholar. Inclusion criteria covered primary studies (both experimental and observational) within disaster settings, published between 2013 and 2023. A total of 25 eligible studies were analyzed. Results: Most studies reported that supplementation with micronutrients particularly vitamin A, vitamin D, zinc, vitamin C, and iron was associated with reduced incidence and severity of respiratory tract infections, diarrhea, and pneumonia. Multi-micronutrient interventions proved more effective than single-nutrient approaches. However, implementation in emergency contexts remains limited, and vulnerable groups beyond young childrensuch as adolescent girls, pregnant women, and the elderlyare often underrepresented in the literature. Conclusion: Micronutrient supplementation has substantial potential to strengthen post-disaster health resilience. Integrating micronutrient strategies into emergency logistics, conducting targeted nutritional screening, and enhancing multi-sectoral training are essential steps toward improving disaster response outcomes.